Nanoindentation Size Effect of Tungsten Single Crystal. Issue 12 (December 2017) - Wen, Zhang; Xuanqiao, Gao; Pingxiang, Zhang; Zhongwu, Hu; Laiping, Li; Jun, Cheng
Abstract: The load-displacement curves, elastic modulus, indent morphology, nanohardness and elastic recovery of high purity tungsten single crystal were investigated by nanoindentation and scanning probe microscopy. Results show that W (111) crystal plane undergoes elastic deformation and plastic deformation during the loading-unloading process, and the load-displacement curve does not show discontinuity, which demonstrates that cracks and brittle fracture are not formed in the indents. Moreover, the pile-up behavior around indents reveals that tungsten single crystal has a low work hardening tend. The nanohardness and elastic modulus of tungsten single crystal were measured by continuous stiffness measurement (CSM), and a size effect on the nanohardness and elastic modulus of tungsten single crystal was observed, which decrease with the increase of indentation depth. The Nix-Gao model was employed to analyze the nanoindentation mechanical characteristics of tungsten single crystals, and the characteristic length ( h * ), the intrinsic hardness in the limit of infinite depth ( H 0 ) and size effect index ( m ) were calculated to be 1490 nm, 6.79 GPa and 0.18, respectively, which indicates that tungsten single crystal has a significant size effect when the indentation depth is below 1490 nm, and the size effect becomes more insignificant when indentation depth is above 1490 nm. When the impression is deeper than 2450 nm, the nanoindentation size effect on the hardness will disappear.